Characterization of Tritium Isotopic Permeation Through ARAA in Diffusion Limited and Surface Limited Regimes. (3rd October 2017) - Zhang, Hongjie; Ying, Alice; Abdou, Mohamed; Shimada, Masashi; Pawelko, Bob; Cho, Seungyon
Abstract: A mathematical model for permeation of multi-components (H2, T2, HT) through a RAFM (Reduced activation ferritic/martensitic) membrane was described based on kinetic theory. Experimental conditions of tritium permeation for ARAA (Advanced Reduced Activation Alloy) material performed at INL were recreated in simulations for model validation. Both numerical simulations and experimental data indicated that the presence of hydrogen reduces tritium permeation rate significantly in low tritium partial pressure with 1000 ppm (0.1%) hydrogen-helium gas mixture at 1atm. Experimental behavior of tritium permeation flux dependence on tritium isotope partial pressure confirmed the kinetic theory. i.e., it still follows diffusion-controlled, square root dependence, with T2 partial pressures and a linear dependence HT pressure even though it is in a diffusion-controlled regime. In addition, the numerical model was validated with literature data for mono-isotope permeation through oxidized and clean MANET II (MArtensitic for NET) samples under surface-controlled and diffusion-controlled regimes. The simulation results agreed well with the experimental data, which indicated that the mono permeation rate through the oxidized sample is much lower ( 2 orders) than clean sample and the permeation rate is proportional to p 1 and p 0.5 for oxidized and clean MANET II samples, respectively.